A 3D printed liquid metal emulsion for low stress activated stretchable electronics. (February 2023) - Sánchez Cruz, Ramón E; Zopf, Stephanie F; Boley, J William
A strain-induced electrically conductive liquid metal emulsion for the programmable assembly of soft conductive composites is reported. This emulsion exhibits the shear yielding and shear thinning rheology required for direct ink writing. Examples of complex self-supported 3D printed structures with spanning features are presented to demonstrate the 3D printability of this emulsion. Stretchable liquid metal composites are fabricated by integrating this emulsion into a multi-material printing process with a 3D printable elastomer. The as-printed composites exhibit a low electrical conductivity but can be transformed into highly conductive composites by a single axial strain at low stresses (< 0.3 MPa), an order of magnitude lower than other mechanical sintering approaches. The effects of axial strain and cyclic loading on the electrical conductivities of these composites are characterized. The electrical conductivity increases with activation strain, with a maximum observed relaxed conductivity of 8.61 × 10 5 S⋅m −1, more than 300% higher than other mechanical sintering approaches. The electrical conductivity of these composites reaches a steady state for each strain after one cycle, remaining stable with low variation (< 6 % standard deviation) over 1000 cycles. The strain sensitivities of these composites are quantitatively analyzed. All samples exhibit strain sensitivities that are lower than a bulk conductor throughout all strains. The printed composites showed low hysteresis at high strains, and high hysteresis at low strains, which may be influenced by the emulsion internal structure. The utility of these composites is shown by employing them as wiring into a single fabrication process for a stretchable array of LEDs.